Comparison of handrail reaction forces between two different handrails during sit-to-stand movement in the elderly. (December 2020) - Kato, Tomohisa; Sekiguchi, Yusuke; Honda, Keita; Izumi, Shin-Ichi; Kanetaka, Hiroyasu
Abstract: Background: The handrail is an effective means of assisting sit-to-stand movements. As some elderly people need force to support their body during sit-to-stand movements because of instability and weakness; however, few handrails are specifically shaped to generate more force and support the body. This study aimed to investigate the effect of a newly designed curved-angled handrail on the reaction force during sit-to-stand movements in the elderly. Methods: Twenty-one elderly subjects (age range, 72–84 years) participated in the study. They performed sit-to-stand movements using a conventional vertical handrail and then the curved-angled handrail five times each. For each subject, body coordinate data were acquired and the handrail reaction force was measured using motion analysis and load sensors on the handrail. Findings: The reaction forces generated in the anterior–posterior and upward–downward directions during sit-to-stand movements using the curved-angled handrail were significantly greater than those generated using the conventional vertical handrail ( p  < .001). Interpretation: Compared with using the conventional vertical handrail, using the curved-angled handrail enhances the generated force during sit-to-stand movements. Highlights: Reaction force generated: curved-angled handrail > conventional vertical handrail Subjective evaluation is also better with curved-angled handrail. Center of mass variations are equal between these two types of handrails.